A Rare Shape of Placenta; Placenta Bipartite, Bilobata, Dimidiate, Duplex: A Rare Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Placenta bipartite is a rare variation of placental morphology. The estimated incidence is up to 2-8 % of pregnancy. There is no distinct racial, ethnic or geographical prediction observed. The diagnosis of an anomalous placenta is important for patient management at the time of delivery. Specifically, the bilobed placenta can be associated with first-trimester bleeding, polyhydramnios, abruption, and retained placenta. Careful attention to the cord insertion is also required for optimal fetal management. We report a case of a 24 years multi gravida with previous history of 2 C/S who had regular antenatal checkup and her pregnancy was uneventful till 36 wks. Her early USG at 16 weeks showed low lying placenta little away from the internal os of cervix. She was advised to take complete bed rest, avoid journey and coitus. Couple was warned about pervaginal bleeding, which may occur any time and also advised to ready at least four blood donors. Her 2nd USG scan at 26wks showed placenta bipartite and insertion of cord over the internal os of cervix. Patient was treated conservatively and dose of inj. Oradexon was completed at 32wks for lung maturation. At 36 weeks, patient perceived less foetal movement and then emergency LUCS with BLTL was done. Baby was well and her postpartum period was uneventful.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 101-103